Theoritical Implementation As Folklore Digital Reconstruction In Malay Literature Education - Wahid, Mohd Effizan; Ain, Rosnidar (Idealogy Journal; Vol 8 No 2 (2023): Idealogy Journal (September 2023)DO - 10.24191/idealogy.v8i2.447, 2023)
Folklore encompasses a variety of aspects, whether narratives or in other formats, and it needs to be moulded into a more creative and innovative form in line with the revolution of this century. Folklore which conveys messages underlying the expression of feelings of society can be categorised into two forms, i.e. narratives and non-narratives or the ones that are told in prose and poetry. The intrinsic values and lessons in the storytelling of folk tales are sub-primary elements in folk literature that can create deep learning in learners. For literary works to have a significant impact on literary education, they must take into account the evolving interests and demands of today's learners. In addition to emphasising the value of folklore teachings offered to secondary students, folklore education should be prioritised in the adult education curriculum. Folklore research has been done from a variety of angles, primarily qualitative ones in the language and semantic domains. Despite this, several literature reviews noted that some folklore studies using other methodologies are still insufficient. Therefore, this concept paper outlines theoretical adaptation, which can be implemented in folklore studies particularly to develop a new module. The aspects of the discussions are based on theoretical andragogy literature reviews by Knowles (1996), and Vygotsky Social Constructivism (1978), which can be applied in folklore learning. As a suggestion, this theoretical discussion will serve as the foundation for literary studies in transition to digital reconstruction using Richey and Klien's (2007) Development and Design Research (DDR) to design and build a new innovative module, a model, guideline, a framework or even an instrument, particularly as an added value in teaching and facilitation in the field of the Malay literature education. KEYWORDS: Adragogy Theory, Social Constructivism Theory, Design & Develop t men Research (DDR), Folklore, Malay Literature Education.